SISTEM PAKAR DIAGNOSIS PENYAKIT GIGI DAN MULUT DENGAN METODE DEMPSTER-SHAFER BERBASIS WEB (Science and Technology (SciTech), 2023)
Health problems are beginning of various disease where the pain experienced is unknown the cause. This pain makes the body becomes weak and can’t perform all activities as well. The mouth is the first organ where the digestive process is very important and must be maintained. In the mouth there are a vital organ it’s called the teeth that serve to help the digestive process by refining the food and helping in speaking smoothness. Therefore, the dental health is very important. Generally, the people often underestimate dental health problems, they are more concerned with the health of other organs. In fact, the dental disease if not treated immediately and as soon as possible, it can harm the other organs. By utilizing the expert system diagnosis of dental and oral disease with dempster-shafer method, the author hope to help the patients to identify the oral disease suffered because the method has advantages can give a believe value for the diagnosis of the disease even with a small value.